A Study on Poverty Alleviation Programmes in India and Its Efforts to Reduce Poverty: Challenges and Strategies in Targeting Rural Poverty (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The aim of this study is Poverty Alleviation Programmes in India and its efforts to reduce Poverty. The poverty alleviation programmes in India can be categorized according to their targets and formations. Most of the programmes are designed to target rural poverty as the prevalence of the poverty is high in rural areas. Moreover, targeting of the poor is challenging in rural areas due to various geographic and infrastructure limitations.